The Implementatio of the Blended Learning Technologies at the Higher Military Educational Institution: Features of the Readiness Formation of the Future Special Purpose Specialists for Professional Activity - Rudynskyi, Vitaly (Educological discourse, 2024)
The technology of blended learning, which combines the advantages of traditional classroom and electronic learning, is considered. It is noted that blended learning is characterized by a double significance (personally significant educational activity and proper organization of educational activity in electronic and traditional format), which contributes to the development of a cadet of a military educational institution as a subject of self-education, and forms his readiness for self-development in the future professional activity. An analysis of the features and essential characteristics of blended learning technology was carried out, its models were investigated, and approaches to introducing blended learning into the educational process of cadets of higher military educational institutions were described. The critical characteristics of blended learning, such as individualization of learning, productive, independent work, appropriate use of classroom time, active implementation of modern information and communication technologies, etc., are highlighted. The interaction of subjects: the teacher, students, electronic educational resources, and the roles assigned to them in the blended learning model are characterized. Electronic resources for implementing blended learning into practice (Google for Education cloud services with basic applications) are considered. The experience of using blended learning technology in the teaching process is described, which is implemented in the form of a three-stage educational model - independent work of cadets (viewing video materials to familiarize themselves with the theoretical material for this lesson, independent performance of tasks to check understanding of the reviewed material), classroom work (active types of educational activity) and post-audit work (independent generalization of the studied educational material). It was concluded that the introduction of blended training into the educational process of future particular purpose specialists, as well as its practical use at higher military educational institutions, contributes to the formation of cadets’ readiness for the activities of future military officers.